Stellar flare oscillations: evidence for oscillatory reconnection and evolution of MHD modes. Issue 2 (11th January 2018) - Doyle, J G; Shetye, J; Antonova, A E; Kolotkov, D Y; Srivastava, A K; Stangalini, M; Gupta, G R; Avramova, A; Mathioudakis, M
Abstract: Here, we report on the detection of a range of quasi-periodic pulsations (20–120 s; QPPs) observed during flaring activity of several magnetically active dMe stars, namely AF Psc, CR Dra, GJ 3685A, Gl 65, SDSS J084425.9+513830, and SDSS J144738.47+035312.1 in the GALEX NUV filter. Based on a solar analogy, this work suggests that many of these flares may be triggered by external drivers creating a periodic reconnection in the flare current sheet or an impulsive energy release giving rise to an avalanche of periodic bursts that occur at time intervals that correspond to the detected periods, thus generating QPPs in their rising and peak phases. Some of these flares also show fast QPPs in their decay phase, indicating the presence of fast sausage mode oscillations either driven externally by periodic reconnection or intrinsically in the post-flare loop system during the flare energy release.